STRATEGI PENGURANGAN RISIKO BENCANA BERBASIS PEMBERDAYAAN MASYARAKAT DESA PENYANGGA KAWASAN KONSERVASI TAMAN NASIONAL GUNUNG MERAPI - Diah Ayuretnani Handayani; Anwar Kurniadi; Fauzi Bahar (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
Mount Merapi National Park (TNGM) is one of the conservation management that conducts community empowerment activities to support disaster risk reduction. Social interaction is one of the capacity-building in disaster management to reduce disaster risk. This research aims to analyze the strategy of empowering the buffer village communities in terms of implementing the management of TNGM conservation areas on disaster management. This study method is qualitative and descriptive through data collection from related documents and literature studies. Based on the results, TNGM has 32 living buffer villages and dependently uses natural resources around the TNGM conservation area. Social interaction with local wisdom is a capacity building in disaster management to reduce disaster risk. The analysis showed that the empowerment of communities has the function of maintaining, saving, and sustaining the conservation areas. However, developing community participation in regional management can be achieved through community empowerment which can be carried out through cooperation/partnering and establishing community groups to manage the areas. In that way, it can create community resilience and reduce disaster risk.